2019
DOI: 10.3390/medicina55020035
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc Score as an Independent Predictor of Suboptimal Reperfusion and Short-Term Mortality after Primary PCI in Patients with Acute ST Segment Elevation Myocardial Infarction

Abstract: Background and objectives: We aimed to demonstrate the clinical utility of CHA2DS2-VASc score in risk assessment of patients with STEMI regarding adverse clinical outcomes particularly no-reflow phenomenon. Materials and Methods: We designed a retrospective cohort study using the data of Tehran Heart Center registry for acute coronary syndrome. The study included 1331 consecutive patients with STEMI who underwent primary angioplasty. Patients were divided into two groups according to low and high CHA2DS2-VASc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 38 publications
4
23
1
Order By: Relevance
“…This study found that increased CHA2DS2-VASc score is an independent predictor of mortality rather than a surrogate measure only. This was in agreement with other studies [6][7][8].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This study found that increased CHA2DS2-VASc score is an independent predictor of mortality rather than a surrogate measure only. This was in agreement with other studies [6][7][8].…”
Section: Discussionsupporting
confidence: 94%
“…This study had con irmed enhanced mortality and morbidity in the presence of no-re low phenomenon. Other studies [5,6,16] displayed independent predictive role of diabetes mellitus, which was similar to the results of this study. However, it was found a borderline statistical signi icance for this relationship.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations